DEVELOPING TEACHING MATERIAL OF DIRECT PROPORTION BASED ON AGRICULTURAL CONTEXT - Riya Apriyani; - Somakim; - Darmawijoyo (Jurnal Kependidikan, 2017)
This study was aimed at designing the valid and practical teaching material of direct proportion using PMRI agricultural contexts. PMRI is one of learning approaches that is able to support the quality of direct proportion learning in schools as well as to determine the potential effects on students’ problem-solving abilities. The study was research and development covering the stages of preliminary and formative study (self evaluation), expert review, one-to-one and small group), and field test. Expert Judgement was used to examine the validity of the teaching material while the small group test was used to examine the practicality of it. The subjects were the students of Grade VII Class A of State Junior High School 1, Air Kumbang. Findings show that the study has produced direct proportion learning material that is valid and practical. Besides validity and practicality, the material has potential effects as seen from the field test. It can be seen from the students’ classical achievement and improvement in problem solving skills to become 66.67%PENGEMBANGAN BAHAN AJAR PERBANDINGAN SENILAI BERBASIS KONTEKS PERTANIANPenelitian ini bertujuan untuk menghasilkan bahan ajar perbandingan senilai yang valid dan praktis menggunakan konteks pertanian berbasis Pendidikan Matematika Realistik Indonesia (PMRI). PMRI adalah salah satu pendekatan pembelajaran yang dapat meningkatkan kualitas pembelajaran perbandingan senilai di sekolah dan untuk mengetahui efek potensial terhadap kemampuan pemecahan masalah siswa. Penelitian ini merupakan penelitian pengembangan yang meliputi tahapan preliminary dan formative study (self evaluation, expert review, one-to-one, dan small group) dan field test. Subjek penelitian ini adalah siswa kelas VIIA SMP Negeri 1 Air Kumbang. Pengumpulan data menggunakan teknik walk through, observasi, dan tes. Expert judgement dilakukan untuk menguji tingkat kevaliditasan sedangkan small group test dilakukan untuk menguji tingkat kepraktisan bahan ajar. Dari hasil penelitian dapat disimpulkan bahwa penelitian ini telah menghasilkan bahan ajar perbandingan senilai yang valid dan praktis. Selain valid dan praktis, bahan ajar ini mempunyai efek potensial dilihat dari field test. Hal ini dilihat dari hasil yang diperoleh siswa secara klasikal memiliki peningkatan dalam kemampuan pemecahan masalah baik yaitu menjadi 66,67%